Performance promotion of broiler chickens: the role of the food supplements - Sinan Abdullah (Basrah Journal of Veterinary Research)
In order to increase egg and chicken meat production, poultry growth is critical. The purpose of this study is to see how well broiler chickens perform when provided different additives in their meals (trace minerals and vitamins). Nutraceuticals, in addition to providing nutritional requirements for birds, offer advantageous pharmacological effects, such as assisting in the establishment of normal state of physiological health, preventing various diseases, and thus improving production performance. The vitamins, polypeptides and amino acids, minerals, enzymes, and other nutraceuticals are examples. Vitamins are dietary substances that are required for vital cell functions such as cell development, growth, and metabolism process. Mineral nutrition is critical in broiler chicken production, with an emphasis on manganese (Mn), zinc (Zn), selenium (Se) and copper (Cu). Due to the availability of organic trace elements and today''s fast-growing birds, broiler chickens'' Mn, Zn, Se, and Cu requirements must be revised.